2007
DOI: 10.1093/nar/gkm347
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of in vivo-assembled pre-mRNA splicing complexes expands the catalog of participating factors

Abstract: Previous compositional studies of pre-mRNA processing complexes have been performed in vitro on synthetic pre-mRNAs containing a single intron. To provide a more comprehensive list of polypeptides associated with the pre-mRNA splicing apparatus, we have determined the composition of the bulk pre-mRNA processing machinery in living cells. We purified endogenous nuclear pre-mRNA processing complexes from human and chicken cells comprising the massive (>200S) supraspliceosomes (a.k.a. polyspliceosomes). As expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
121
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 100 publications
6
121
1
4
Order By: Relevance
“…Cwc23p was first found as a copurifying protein with the Cef1p splicing factor (Ohi et al 2002) and was subsequently identified in other spliceosomal preparations Chen et al 2007). Alternatively reported as essential (Giaever et al 2002) or nonessential (Tizon et al 1999), we find the cwc23TKAN null mutant to be viable but sickly.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Cwc23p was first found as a copurifying protein with the Cef1p splicing factor (Ohi et al 2002) and was subsequently identified in other spliceosomal preparations Chen et al 2007). Alternatively reported as essential (Giaever et al 2002) or nonessential (Tizon et al 1999), we find the cwc23TKAN null mutant to be viable but sickly.…”
Section: Discussionmentioning
confidence: 59%
“…At least two DnaJ proteins, DNAJC8 and DNAJC13, copurify with the mammalian spliceosome but neither one has been studied for function in splicing ( Jurica et al 2002;Chen et al 2007). Removal of much of the DnaJ motif from yeast Cwc23p has little obvious consequence on splicing, growth, or this protein's interaction with Spp382p.…”
Section: Discussionmentioning
confidence: 99%
“…3), together with the previous report that RBM5 stable transformants of lung cancer cell lines undergo apoptosis (29), supports the role of RBM5 as an apoptosis regulator in cancer cells. RBM5 is localized in nuclei and associated with spliceosomal complexes (26,35,36). Our work here indicates that RBM5 binds to casp-2 pre-mRNA and regulates the balance of casp-2L versus casp-2S splicing isoforms, uncovering a previously unknown activity of RBM5 as a splicing regulator.…”
Section: Discussionmentioning
confidence: 61%
“…S5B) (27). Interestingly, ZFP106, SF3A2, and ZFR all contain a specific C2H2 ZnF motif (C-X 2 -C-X 12 -H-X 5 -H) that was previously identified to be conserved in Matrin 3 (MATR3) and several other RNA-binding proteins, which differs from the typical DNA-binding C2H2 ZnF motif (Fig.…”
Section: Resultsmentioning
confidence: 88%